Improving the Manufacture by Flexographic Printing of RFID Aerials for Intelligent Packaging - CAITLIN MCCALL (2023)
Flexography is a well-established high-volume roll-to-roll industrial printing process that has shown promise for the manufacture of printed electronics for smart and intelligent packaging, particularly on to flexible substrates. Understanding is required of the relationship between print process parameters, including ink rheology, and performance of printed electronic circuits, sensors and in particular RFID antenna. The complexity of this printing process with its shear and extensional flows of complex inks and flexible substrates can lead to undesirable surface morphology to the detriment of electronic performance of the print. This thesis reports work that progresses the understanding of the complex relationships amongst relevant factors, particularly focusing on the printability of features that have an impact on printed RFID antenna where increases in resistance increase the antennas resonant frequency. Flexography was successfully used to print RFID antenna. However, the large variation in print outcomes when using commercial inks and the limits on resistivity reduction even at the optimal print parameters necessitated the systematic development of an alternative silver flake ink. Increases in silver loading and TPU polymer viscosity grade (molecular weight) increased the viscosity. The ink maintained its geometry from the anilox cell between rollers, on to the substrate and print surface roughness increased. This, however, did not increase resistance of the track due to the high silver loading. Better understanding of the relationship between print parameters, print outcomes, ink rheology and performance of an RFID antenna has been achieved. Increases in silver loading up to 60wt.% improved conductivity. However, further increasing the silver loading produced negligible additional benefit. An adaption of Krieger-Dougherty suspension model equation has been proposed for silver at concentrations over 60wt.% after assessing existing suspension models. Such a model has proven to better predict relative viscosities of inks than Einstein-Batchelor, Krieger-Dougherty and Maron-Pierce equations. Increasing TPU viscosity grade was found to be a promising ink adjustment in the absence of changing print parameters, to produce a more consistent print. Better prediction of ink behaviour will allow for improved control of ink deposition, which for RFID applications can improve ink conductivity, essential for good response to signal. Further developments such as addition of non-flake particles and formulation refinement are required to enable the model ink to match the resistivity of the commercial ink.